Disulfide bond formation of thiols by using carbon nanotubes. Issue 17 (19th April 2017) - Hirano, A.; Kameda, T.; Sakuraba, S.; Wada, M.; Tanaka, T.; Kataura, H.
Abstract : Carbon nanotubes induce disulfide bond formation of thiols over a wide pH range, which affects protein folding in biological systems. Abstract : Clarification of the interactions between carbon nanotubes (CNTs) and proteinogenic amino acids is a key approach to understanding CNT–protein interactions. Previous studies have addressed the mechanism of the physical adsorption of amino acids onto CNTs. However, little is known about their chemical reactions in aqueous solutions. Here, we established dispersant-free systems to clarify intrinsic CNT–thiol interactions. We demonstrated that the redox reaction of CNTs with cysteine, containing a thiol group, leads to disulfide bond formation between cysteine molecules, even under acidic conditions. The generality of the redox reaction is validated using other thiols such as dithiothreitol and glutathione. The present results suggest that structures of proteins and peptides containing free thiol groups are chemically modified and misfolded on CNT surfaces by this disulfide bond formation in biological systems.